SOSIALISASI TENTANG PENTINGNYA KESADARAN DALAM MEMBERIKAN PERSEMBAHAN KEPADA TUHAN DI JEMAAT GKSI PELITA HARAPAN LEMBOKODI - Emanuel Kristinus Ndruru; Devi Kristi Susanti; Salome Salome; Umbu Ndapa Kahali (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
Based on observational research, many GKSI Pelita Harapan Lembokodi congregation members do not give offerings properly due to economic factors. The problems prompted a service activity to the congregation at the GKSI Pelita Harapan Lembokodi church to increase the congregation's awareness of Lembokodi. Even so, there are shortcomings that need to be evaluated by the church because the congregation's appreciation of God's blessings is not balanced with their knowledge about giving offerings. The church must evaluate such conditions. The methods used in writing this research article are interviews with congregants and literature studies to support valid data. This socialisation activity requires 2 (two) stages to get better results. The results obtained after this activity was carried out showed that there was a change in the attitude of the congregation's awareness of giving offerings to God. This activity aims to answer the importance of awareness and lead to the congregation's situation by expanding knowledge and discussing ways to help the congregation improve their spirituality to grow and be rooted in the knowledge of Jesus Christ.